Seismic behavior of the contents of seismically isolated buildings - Qadus, Zakirullah Haji Abdul (İstanbul Kültür Üniversitesi / Lisansüstü Eğitim Enstitüsü / İnşaat Mühendisliği Ana Bilim Dalı / Yapı Mühendisliği Bilim Dalı, 2021)
Sismik izolasyon, gelişmekte olan depreme dayanıklı bir tasarım teknolojisidir. Özellikle ankastre binalara kıyasla kat ivmelerini azaltır. Böylece, binaların içeriğini korumada çok başarılıdır. Önceki çalışmalarda, içerik korumanın kapsamı yalnızca kat ivmelerinin incelenmesi ile yapılmıştır. Bununla birlikte, özellikle elektronik cihazlar, bilgisayarlar, test makineleri vb. titreşime duyarlı içerikler binaların çeşitli katlarına monte edilmiş raflarda yer almaktadır. Bu nedenle, sadece kat ivmelerini hesaba katmak yerine raf katlarındaki ivme düzeylerini değerlendirmek gerekir. Bu konuya ışık tutmak amacıyla, bu tezde sismik izolasyonlu binaların farklı seviyelerinde yer alan farklı doğal periyotlara sahip rafların ivme tepki davranışı değerlendirilmektedir. Bina, tarihi ve sentetik yakın fay yer hareket kayıtlarına tabi tutulduğunda bina ve raf sistemleri, bina-raf etkileşimini hesaba katan birleşik bir yapısal sistem olarak modellenmiştir. Sonuçlar, belirli ivme eşiği sınırları göz önüne alındığında karşılaştırmalı grafikler ve başarısızlık olasılıkları şeklinde rapor edilmiştir

Seismic isolation is an emerging earthquake resistant design technology. It particularly reduces floor accelerations as compared to fixed base buildings. Thus, it is very successful in protecting the contents of buildings. In previous studies, the extents of the content protection was assessed by investigating the floor accelerations only. However, particularly vibration sensitive contents such as electronic devices, computers, testing machines, etc are located on racks which are mounted on various floors of buildings. Therefore, it is essential to assess the acceleration levels sustained at the rack floors rather than just taking floor accelerations into account. In order to shed light to this issue, in this thesis, acceleration response behaviour of benchmark racks with rack natural periods that are located at different levels of a benchmark seismically isolated building are assessed when the building is subjected to historical and synthetic near-fault ground motion records. The building and the rack systems are modelled as a combined structural system which takes the building-rack interaction into account. Results are reported in the form of comparative plots and failure probabilities when certain acceleration trash hold limits are considered.
Sismik izolasyonlu binalardaki içeriğin sismik davranışı
Keywords: İnşaat Mühendisliği; Civil Engineering